Training Staff of Afterschool Programs on Healthy Eating and Physical Activity: Opportunity to Reduce Childhood Obesity. (December 2019) - Nerud, Kimberly; Steiner, Matthew
Escalating obesity rates among children across the nation has prompted interest in investigating the role of afterschool programs in the promotion of healthy eating and physical activity among participating children. This approach facilitates intervention programs that will be supported in daily routines of staff. Children need positive role models; the work could be a challenging process and will require staff willingness and assistance.